Ingresos tributarios por impuesto a la renta y su relación con la asignación de recursos en el distrito de Punchana periodo 2020 – 2023 - Dávila López, Yasmine Jesabel (2025)
Tax collection is key to financing essential services and promoting sustainable development, but in Peru it faces challenges such as high informality, inefficiency in public management and low citizen knowledge about its importance and allocation. Therefore, the purpose of this research is to identify how tax revenues from income tax are related to the allocation of resources in the Punchana district period 2020-2023, with a quantitative and longitudinal approach, with a non-experimental correlational design, which had as population the data of tax revenues from income tax and the allocation of resources, the study showed a sustained growth in both variables, although without a statistically significant relationship, which suggests that the allocation of resources does not depend exclusively on local collection, but on other factors, highlighting Third Category Income as the main source of income (49.12%) and Fifth Category Income as the second most relevant (31.47%). Despite a slight drop in 2023, the general trend in tax revenues has been positive. On the other hand, resource allocation grew by S/ 7,167,678.00, prioritizing investment in non-financial assets and personnel spending, indicating a reorientation towards infrastructure and labor spending. It is concluded that the evolution of both variables responds to a combination of structural and cyclical factors, so it is recommended to strengthen the efficiency of public spending and diversify the tax base to guarantee fiscal sustainability.